EFISIENSI MATERIAL PADA PEMBANGKIT LISTRIK TENAGA NUKLIR LWR (LIGHT WATER REACTOR) DAN PHWR (PRESSURIZED HEAVY WATER REACTOR) - Mohammad Ahied (JURNAL PENA SAINS, 2015)
This article  analyze models of nuclear reactors from nuclear power plants the LWR (Light Water Reactor), which consists of BWR (Boiling Water Reactor) and PWR (Pressurized Water Reactor) and PHWR (Pressurized Heavy Water Reactor). Analyzed qualitatively its material combination which includes fuel, moderator and cooler to get a reliable and energy efficient processing of various models of the nuclear reactor. From the analysis of the obtained, BWR fuel burn up 30,000 MWD/MTU, and PWR 32.090 MWD/MTU, and PHWR 8000 MWD/MTU, a substance Hydrogen is a good moderator but have a high absorption cross section. Heavy water neutron economy cling to. Moderators can also serve as a coolant for example for LWR and HWR.